Exploring Protagonist Characterization in Assassin’s Creed III (2012): A Transitivity Analysis - Rio Firman Wandana; Wawan Gunawan (Universitas Sanata Dharma, 2025)
Numerous studies suggest that transitivity system is applicable to examine characters in traditional literatures such as novels or short stories. Today, videogame is considered as a modern literary work by offering interactive and innovative way to deliver the narrative. The present study investigates the characterization of Connor Kenway – the protagonist of Assassin’s Creed III (2012) videogame, using transitivity system. This study aims to examine the identified process types in terms of their contributions to Connor’s characterization. This study employs Creswell (2018) descriptive qualitative method involving textual analysis of the dialogues in the videogame. The dialogues were transcribed and analyzed following the concepts of Systemic Functional Linguistics on transitivity system. The study applies purposeful sampling technique, in which the data are categorized into three groups; dialogues spoken by Connor himself, the supporting characters, and the villain characters. Focusing on the use of transitivity system, the analysis found that the identified transitivity processes uniquely construe the portrayal of Connor’s complex characterization. Firstly, he is portrayed as a vengeful man. Secondly, he is portrayed as an intelligent man with high cognitive abilities. Thirdly, he is portrayed as a hero and savior according to the supporting characters while also as a criminal and savage according to the villain characters. Fourthly, he is portrayed as a man with cautious nature. Lastly, he is portrayed as a useful informant. The result of this study suggests that transitivity system is a versatile tool for examining the portrayal of characterization in videogames.